ETHICAL CONSIDERATIONS REGARDING GENETIC DISCRIMINATION IN THE CASE OF HUNTINGTON’S DISEASE - Dumache Raluca; Puiu Maria; Ciocan Veronica; Muresan Camelia; Enache Alexandra (European Scientific Journal, ESJ, 2015)
Huntington’s is a genetic neurodegenerative disease with dominant autosomal transmission, and high penetrance. This transmission model represents a high recurrence risk (50%) in case of the descendants of affected individuals. This disease can have its debut during adulthood, 40-50 years old or, in case of its juvenile form, during childhood or adolescence. The disease evolves with dystonia, choric movements, rigidity and dementia. Genetic testing for HD mutation is performed through molecular techniques and is possible at any age, independent of whether the person is symptomatic or asymptomatic. The genetic testing allows the identification of those individuals who are carriers of mutations on certain genes, these mutations being the underlying cause for some genetic diseases. At the present moment there are 3 types of genetic testing: diagnostic, carrier and predictive. The predictive tests identify whether an individual is a carrier for a certain specific genetic mutation and whether the possibility exists for him to develop certain health issues later on. Being aware of the carrier status for a certain genetic mutation for Huntington’s represents an element with major impact on the individual and on their family and can lead to discrimination from the side of the insurance companies, employers as well as others.